Advances in public policies and epidemiological surveillance related to the human immunodeficiency virus/AIDS in Ecuador - Joshua Daniel Govea Intriago; Patricio Damián Mayorga Medina; Francisco Xavier Poveda Paredes (Medisur)
The human immunodeficiency virus is one of the main health problems worldwide. It is recognized as a multifactorial phenomenon, where public policies regarding prevention, timely diagnosis and treatment are key. The objective of this study is to describe the advances in public policies and epidemiological surveillance related to the human immunodeficiency virus/AIDS in Ecuador. Important steps are evident in relation to political commitment and social responsibility to stop the injuries of the human immunodeficiency virus/AIDS, and sexually transmitted infections, based on strategies focused on prevention, as well as prophylactic, antiretroviral, and treatment patient follow-up. Some projects have been implemented aimed at fulfilling what was agreed in the United Nations declaration, and within the framework of the national development plan. Difficulties persist related to access to virus diagnosis and follow-up tests, mainly due to the concentration of these in a single institution.